Discrimination of Malignant versus Benign Mediastinal Lymph Nodes Using Diffusion MRI with an IVIM Model. - Qi, Li-Ping; Yan, Wan-Pu; Chen, Ke-Neng; Zhong, Zheng; Li, Xiao-Ting; Cai, Kejia; Sun, Ying-Shi; Zhou, Xiaohong Joe (European Radiology, 2018)
Objectives: To investigate the value of an intravoxel incoherent motion (IVIM) diffusion model for discriminating malignant versus benign mediastinal lymph nodes (MLN).Methods: Thirty-five subjects with enlarged MLN were scanned at 1.5 Tesla. Diffusion-weighted imaging was performed with eight b-values. IVIM parameters D, D*, and f, as well as apparent diffusion coefficient (ADC) from a mono-exponential model were obtained. 91 nodes (49 malignant and 42 benign) were analysed with pathologic (n=90) or radiologic (n=1) confirmations. Receiver operating characteristic (ROC) analysis was used to evaluate the diagnostic performance.Results: The mean values of D, ADC, and f for the malignant group were significantly lower than those for the benign group (p<0.001), while D* showed no significant difference (p=0.281). In the ROC analysis, the combination of D and f produced the largest area under the curve (0.953) compared to ADC or other individual IVIM parameters, leading to the best specificity (92.9%) and diagnostic accuracy (90.1%).Conclusion: This study demonstrates that the combination of IVIM parameters can improve differentiation between malignant and benign MLN as compared to using ADC alone.Key Points: • Diffusion MRI is useful for non-invasively discriminating malignant versus benign lymph nodes. • A mono-exponential model is not adequate to characterise diffusion process in lymph nodes. • IVIM model is advantageous over mono-exponential model for assessing lymph node malignancy. • Combination of IVIM parameters improves differentiation of malignant versus benign lymph nodes.